PEMANFAATAN MEDIA SOSIAL DALAM MEMBANGUN AWARENESS MASYARAKAT TERHADAP KESEHATAN TELINGA (STUDI KASUS PADA AKUN MEDIA SOSIAL INSTAGRAM @ruangmendengar) - Cahya Assyura (2022)
The development of technology and social media is currently very helpful for society. Instagram now is a popular social media among the public because of its convenience, it provides to share information widely and quickly. The lack of information about ear health in Indonesia makes Ruang Mendengar being the first digital platform in Indonesia that focuses on discussing ear health. Instagram now can be used to share information about ear health to build awareness to Indonesian people, which is carried out by Ruang Mendengar through their Instagram account namely @ruangmendengar. The purpose of this study is to find out how Instagram social media from Ruang Mendengar can be used to build awareness of the Indonesian people towards ear health. This research uses a qualitative approach with a case study method. The data collection technique was done using in-depth interviews and documentation. The results showed that the communication strategy adopted by Ruang Mendengar was good and effective in building awareness about ear health.